342 Intussusception encephalopathy: a clinically deceptive presentation. (11th October 2021) - Khries, Maymunah; Bellis, Paul; Tse, Yincent; McDonald, Leigh
Abstract : A 7-month-old presented with reduced responsiveness and non-bilious vomiting. On presentation, he was encephalopathic, apyrexial with normal vital signs. Pupils were intermittently miotic and initial abdominal examination was normal. Investigations including blood gas, biochemistry, inflammatory markers, metabolic and toxicology panels were normal. A CT brain scan showed no abnormality. Abdominal examination 24 hours later elicited a possibility of tenderness. Therefore we proceeded with abdominal ultrasound which revealed an evidence of ileocolic intussusception. Initial standard management of ileocolic intussecption was attempted by radiological pneumatic reduction (air enema) which was unsuccessful. Subsequent definitive surgical management achieved by laparotomy and manual reduction successfully released the obstruction. He recovered uneventfully and underwent usual post-surgical care. Discussion: This case illustrates a rare occasion of intussusception presenting as an acute encephalopathy in the absence of typical signs of bowel obstruction. Although uncommon, the recognition of this possibility should be entertained, particularly in an unexplained encephalopathy. A recent study showed about 4% of children diagnosed with intussusception had one or more neurological symptoms recorded at presentation. Lethargy was the most frequent, followed by hypotonia, generalised weakness, paroxysmal events, and fluctuating consciousness. One study reported a series of 13 cases of children whom impairment of the mental state preceded the appearance of common gastrointestinal symptoms. Another distinctive feature is the presence of miosis. The aetiology is unclear but there has been hypotheses that this could be caused by the production of endogenous opioid in response to stress and pain. In conclusion, the incidence of children with bowel aetiology having an altered mental status as a primary presentation is rare. However, as prognosis of intussusception can be time-dependent, early recognition of this possibility by clinicians is crucial in order to minimise serious morbidity and mortality risk.